PERANCANGAN SISTEM INFORMASI E-LIBRARY BERBASIS WEB PADA PERPUSTAKAAN RAKYAT NYALA AKSARA - Pratama, Aditya Putra; Saragih, Saut Pintubipar (Computer Science and Industrial Engineering, 2021)
The library is a place to store books that are managed by an organization and can be read by everyone who visits the library. Libraries today can keep up with the times when everything is digital. Digitizing the library is a new breakthrough that can target a wider audience so that the use of the library becomes greater. Making digital libraries can use object-oriented methods that have entities in them such as use case diagrams, activity diagrams, sequence diagrams, class diagrams. Analyzing digital libraries using the waterfall method, namely analysis, and design.